Hydrochloric Acid Cyclic Exposure Effect on Microleakage of Resin Cements - Nassief, Sarah. (2018)
Abstract: Introduction: Marginal microleakage is one of the major complications associated with bonding to dental porcelain. The extent of microleakage is unpredictable and differs according to the types of cement used. Research has evaluated the effect of common acidic media on the oral cavity and dental restorations. However, little is known about the effect of hydrochloric acid from the stomach in gastroesophageal reflux patients on the microleakage of resin cements under ceramic restorations. Objective: To evaluate microleakage of different resin cements after immersion of zirconia-reinforced lithium silicate crowns (ZLS) in hydrochloric acid (HCl) solution. Materials and Methods: 45 extracted non-carious human molars were prepared for porcelain crowns. Teeth were randomized into three different types of resin cement: RelyX™ UniCem (3M, ESPE), Variolink® Esthetic Dual-cure (Ivoclar Vivadent) and Panavia™ 21 (Kuraray America Inc.). Five replicates were used as a control for each resin cement. ZLS crowns were designed and milled from Celtra® Duo blocks using CEREC CAD/CAM system and then cemented to the prepared teeth using the assigned cement according to the manufacturers' guidelines. Samples were thermal cycled between water temperatures of 5℃ and 55℃ for 5,000 cycles with a 15 second dwell-time after each temperature. In order to mimic one year of clinical time in a patient's mouth, samples of the experiment group were subjected to 91 one hour cycles in HCl (pH 2) followed by one hour in artificial saliva, however samples of the control group were submersed in artificial saliva for 91 hours. After the 91 cycles were completed, specimens were submerged in 50% silver nitrate solution for 24 hours followed by a developer solution for eight hours. The samples were embedded in clear epoxy resin and sectioned in a buccolingual direction at 0.5 mm. Sections were analyzed by a stereomicroscope at a magnification of 10X. Proportion of microleakage was calculated by dividing the total length of the dye penetration by the total length of the restoration. Data were analyzed with the Kruskal-Wallis test and Mann-Whitney U test with the Bonferroni correction. Results: There was a statistically significant difference in median microleakage between the experiment and the control groups (p <0.05) However, there was no statistically significant difference between the three types of cement in the experiment group. Conclusion: Within the limitations of this in-vitro study, the results indicated that all of the resin cements tested in the study exhibited microleakage to some degree, especially when they get exposed to the hydrochloric acid solution.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Other.; Advisor: Ala Ali.; Committee: Vasiliki Tsakalelli, Aikaterini Kostagianni, and Sarah Pagni.; Keyword: Dentistry.